2017
DOI: 10.5812/modernc.68206
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Dental Caries Preventive Behaviors Among Pregnant Women Based on Self-Efficacy and the Theory of Planned Behavior

Abstract: Background and Objectives: Pregnant women's oral and dental hygiene is of great importance to maternal and neonatal health. This study aimed to predict dental caries preventive behaviors among pregnant women based on self-efficacy and the theory of planned behavior. Methods: This cross-sectional descriptive-analytical study was conducted in 2016 on 258 pregnant women recruited from comprehensive healthcare centers in Birjand, Iran. Sampling was done via multistage random sampling. Data collection instrument wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
(15 reference statements)
0
4
3
Order By: Relevance
“…A possible explanation is that our participants were independent adults who made their own decisions. In contrast to our results, other studies conducted in Indonesia and Iran found that subjective norms had a stronger effect on OHBI than attitude [ 33 , 35 ]. This inconsistency may be due to variations in sociodemographic characteristics among the study subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…A possible explanation is that our participants were independent adults who made their own decisions. In contrast to our results, other studies conducted in Indonesia and Iran found that subjective norms had a stronger effect on OHBI than attitude [ 33 , 35 ]. This inconsistency may be due to variations in sociodemographic characteristics among the study subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be due to that human beings are rational, i.e., people perform a behavior if they believe that behavior is significant to them and evaluate its consequences the behavior positively, regardless of their residence. However, this result is inconsistent with studies done in Iran and Indonesia where the subjective norm was found to be the strongest predictor of OHBI [31,34]. This may due to the socio-cultural difference among the study participants.…”
Section: Plos Onecontrasting
confidence: 99%
“…Furthermore, the variables in the theory were found to be strong predictors of oral hygiene intention/behavior by different studies in different ways. For example, ATT, SN and PBC according to studies in Indonesia, Pennsylvania and Northern Ireland [ 29 , 31 , 32 ], ATT and PBC based on studies in Ireland, Canada and Romania [ 24 , 28 , 33 ], and SN according to a study conducted in Iran [ 34 ] were found to be a significant predictor(s) of oral hygiene behavior/intention.…”
Section: Introductionmentioning
confidence: 99%
“…Studies similar to our findings were conducted in Iran, and Indonesia found that perceived norms had a strong influence on behavioral intention in different oral health domains. [ 22 23 ] Compared to our findings, however, a study in by Badri et al [ 24 ] revealed that subjective norms do not influence the behavior of individuals when it comes to dental visit attendance. Another study revealed that perceived norms do not influence Mexican immigrants’ intentions to seek preventive care.…”
Section: Discussioncontrasting
confidence: 85%
“…This finding contradicts previous studies conducted in the context of oral health. [ 16 23 , 25 ] Sutton suggests that the link between these two factors is not strong because of a causal lag. [ 26 ] Due to the scarcity of data, it was difficult to compare our results with the available literature.…”
Section: Discussionmentioning
confidence: 99%